Colloidal gold immunolabeling of immunoglobulin-binding sites and beta antigen in group B streptococci. - Coleman, S E (1990)
We have characterized the immunoglobulin A (IgA)-Fc-binding properties and beta-antigen expression of several strains of group B streptococci by using ultrastructural immunocytochemistry. Colloidal gold-labeled tracers were used with intact and sectioned bacteria in order to gain information regarding the location and distribution of cell surface and cytoplasmic IgA-Fc-binding molecules and beta antigen. Colloidal gold (5- or 15-nm particles) was conjugated to IgA to characterize IgA-binding properties and to IgG to test for IgG binding. Rabbit anti-beta antiserum was reacted with the bacteria and then with protein G labeled with 15-nm colloidal gold particles. A double-labeling technique was used for simultaneous localization of IgA-Fc- and anti-beta-antibody-binding properties on sectioned bacteria. The data corroborated previous results which indicated that (i) IgA-Fc-binding and IgA-Fc-nonbinding forms of beta antigen can be secreted by strains which do not express beta antigen on the cell surfaces (HG806, VC75); (ii) differences in levels of expression of beta antigen and/or IgA-Fc-binding proteins can be detected among various group B isolates; (iii) group B streptococci do not express human IgG-Fc-binding proteins; and (iv) not all forms of beta antigen are capable of binding human IgA.